Central Nervous System Venulitis Presenting as Migraine. Issue 3 (23rd July 2013) - Orr, Serena L.; dos, Marlise P.; Jurencak, Roman; Michaud, Jean; Miller, Elka; Doja, Asif
<x xml:space="preserve">Abstract</x> Objective To describe a case of pediatric central nervous system (CNS) venulitis. Background Primary angiitis of the CNS is a rare but increasingly well‐recognized cause of morbidity in children. It primarily involves the arteries and arterioles of the CNS, with only 1 published case of a pediatric patient found to have isolated CNS venulitis on brain biopsy. Case Report A 17‐year‐old female with a 4‐year history of migraines presented with increasingly frequent migraines and right‐sided hemiplegia. Infectious, hematologic, and rheumatologic work‐ups were negative. Brain magnetic resonance imaging showed multiple rim‐enhancing lesions consistent with calcifications affecting the deep left white matter. On brain biopsy, there was evidence of an inflammatory process involving small veins and venules. The patient displayed clinical improvement with a course of high‐dose steroids and 6 monthly cyclophosphamide infusions followed by maintenance therapy with mycophenolate mofetil. Discussion We describe a case of pediatric CNS venulitis presenting with migraine.